Epidemiologia e fatores de risco das infecções da corrente sangüínea por bactérias gram-negativas multiresistentes e letalidade atribuída em leucemia aguda - Goto, Janaina Midori [UNIFESP] (2010)
chemotherapy, are exposed to various damages against their immunity. Neutropenia is one of the most common and is often related to BSI. Recently, the epidemiology of infections in neutropenic patients experienced frequent changes. GNB bloodstream infections have been increasingly involved in therapeutic challenge, due to the increased resistance, difficulty in empirical therapy and mortality. Knowledge of the epidemiology of BSI and risk factors for acquisition of GNB and MDR-GNB BSI are fundamental for the appropriate treatment of infectious complications. Patients and methods: We conducted a retrospective study of BSI in patients with leukemia, admitted in an university tertiary hospital from 2002 to 2007. Epidemiological description of pathogens of BSI, as well as susceptibility and analysis of risk factors for the acquisition of GNB and MDR-GNB BSI were evaluated. Results: 148 agents were found in 64 patients with leukemia, being 55.4% GNB, 39.2% GPC and 5.4% fungus. The more prevalent agents were SCoN (22.3%), P. aeruginosa (17.6%) and K. pneumoniae (10.8%). Resistance to oxacillin was indentified in 66.7% of SCoN and 34.3% of GNB were multi-drug resistant. Seven day mortality occurred in 20.0% of patients with GPC BSI and in 47.0% of patients with GNB BSI. Neutropenia (p = 0.003, OR 14.060, IC 2.457-80.465) and presence of signs and symptoms of bacteremia (p = 0.002, OR 20.907, IC 2.953-148.001) were factors related to GNB BSI by multivariate analysis. The second multivariate analysis showed that previous use of glycopeptides was independently related to the occurrence of MDR-GNB BSI (p = 0,015, OR = 7,530). The GNB BSI lethality was similar to that found in MDR-GNB BSI (20.4% and 19.1%) but patients with the second one died earlier. Conclusions: in this study, GNB were the most prevalent BSI agents. More than 30% of agents were multi-drug resistant germs. Independent risk factors for the acquisition of BGN were the presence of neutropenia and signs and symptoms at the moment of bacteremia. Previous use of glycopeptide was an independent risk factor for the acquisition of MDR-GNB. Evolution to death occurred in 55% of patients with BSI, being more premature among patients with MDR-GNB.